PERAN BUMDES DALAM MENINGKATKAN EKONOMI MENUJU DESA SEJAHTERA DI DESA MOUTONG - Yolanda Ngabito; Nur Waqiah Dali; Parhamida Suma (Journal of Hulonthalo Service Society (JHSS), 2023)
Village economic development is one of the main priorities in the national development agenda. Village-Owned Enterprises (BUMDes) have a strategic role in driving the economy at the village level. This study aims to examine the role of BUMDes in improving the economic welfare of the community in Moutong Village. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that BUMDes in Moutong Village is able to make a significant contribution to increasing community income through various business units. However, there are challenges in the management and funding aspects that require further attention. This study is expected to be a reference for more effective BUMDes management.